Gambaran Pilihan Sumber Informasi Kesehatan Reproduksi Remaja bagi Mahasiswi Fakultas Ilmu Keolahragaan Universitas Negeri Malang - Alifia Candra Puriastuti; Zumroh Hasanah; Dessy Amalia (Malahayati Nursing Journal, 2024)
ABSTRACT Adolescent reproductive health issues are something that should be taken into account, especially with the increasing number of adolescents due to the demographic bonus in Indonesia, because it has long-term effects on mental and emotional health, financial status, and social well-being, in addition to the physical impacts experienced. It is no wonder that various media are sources for adolescents to obtain reproductive health education. To explore the choice of sources of information related to reproductive health obtained by female students. This study has a descriptive research design, the research population is all female students of the Faculty of Sport Science, State University of Malang, in 2023. The sampling technique used in this study is snowball-random sampling, and 103 female students were obtained as research samples. Most female students choose teachers or lecturers as a source of information, namely sources of puberty information (87.3%) and sources of reproductive system and sexuality information (93.1%). Then followed social media as the next source of information. And female students think that teachers and lecturers are the first and most important sources of information, sources of puberty information for 31 people; and sources of reproductive system and sexuality information for 44 people. So lecturers need to improve their understanding of reproductive health in order to be a good source for students, and female students need to be wise in taking information presented on social media so that the information obtained is correct. Keywords: Adolescent Reproductive Health, Source of Information  ABSTRAK Masalah kesehatan reproduksi remaja merupakan hal yang patut diperhitungkan terutama dengan meningkatnya jumlah remaja akibat bonus demografi di Indonesia, karena memiliki efek jangka panjang pada kesehatan mental dan emosional, status keuangan dan kesejahteraan sosial, selain dampak  fisik yang dialami. Tak ayal berbagai media menjadi sumber bagi remaja memperoleh pendidikan kesehatan reproduksi. Menggali pilihan sumber informasi terkait kesehatan reproduksi yang diperoleh para mahasiswi. Penelitian ini memiliki desain penelitian deskriptif, populasi penelitian seluruh mahasiswi Fakultas Ilmu Keolahragaan Universitas Negeri Malang pada Tahun 2023. Sedangkan teknik sampel yang digunakan dalam penelitian ini adalah snow ball-random sampling dan diperoleh 103 mahasiswi sebagai sampel penelitian. Sebagian besar mahasiswi memilih Guru/Dosen sebagai sumber informasi, yakni sumber informasi pubertas sebesar 87,3% dan sumber informasi sistem reproduksi dan seksualitas sebesar 93,1%. Kemudian disusul media sosial sebagai sumber memperoleh informasi berikutnya. Serta mahasiswi berpendapat bahwa Guru/Dosen merupakan sumber informasi paling penting pertama,  sumber informasi pubertas sebesar 31 orang dan sumber informasi sistem reproduksi dan seksualitas sebesar 44 orang. Sehingga dosen perlu meningkatkan pemahamannya terkait kesehatan reproduksi agar dapat menjadi sumber yang baik bagi mahasiswa dan tidak jauh berbeda, mahasiswi perlu bijak dalam menggambil informasi yang disajikan media sosial agar informasi yang diperoleh benar. Kata Kunci: Kesehatan Reproduksi Remaja, Sumber Informasi